Study of the Contribution of Transformational Leadership, Training and Digital Education Innovation on Teacher Performance in Learning at SMP Muhammadiyah Ngawi - Farita Lina Rodiyah; Bambang Sumardjoko; Sofyan Anif (Budapest International Research and Critics University, 2022)
Teachers as education providers play a role in improving student learning outcomes. The quality of teacher performance is very decisive on the quality of educational outcomes because the teacher is the figure who most often interacts directly with students during the learning process. The purpose of the study was to determine the contribution of transformational leadership, education and training, and educational digital innovation to teacher performance in learning at SMP Muhammadiyah Ngawi. This type of research is causal associative research using a quantitative approach. Places of research in several SMP Muhammadiyah Ngawi. The data analysis technique used multiple linear regression analysis. The results showed that transformational leadership had a positive and significant effect on teacher performance with a significance value of 0.010 < 0.05. The education and training variables have a positive and significant effect on teacher performance with a significance value of 0.013 < 0.05. Furthermore, the education and training has a positive and significant effect on teacher performance 0.001 < 0.05. Taken together, the variables of the transformational leadership, the education and training and the digital innovation on teacher performance are simultaneously influential. Suggestions for the teacher research at SMP Muhammadiyah Ngawi are expected to help each other with the problems of other members in providing information related to teacher performance.